THE INFLUENCE OF RAW MATERIALS AND PRODUCTION PROCESSES ON PRODUCT QUALITY IN THE ROOF TILE INDUSTRY IN SABRANG VILLAGE - Pramesti, Cindy; Sari, Maheni Ika; Hafidzi, Achmad Hasan (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study analyzes the effect of raw material inventory, raw material quality, and production process on product quality in the roof tile industry in Sabrang Village, Ambulu District, Jember Regency. Unlike previous studies that used small samples and focused on large companies, this study used a sample of 80 craftsmen in the rural industry, selected using saturated sampling techniques. The method used is multiple linear regression analysis. The results of the study indicate that the three factors significantly affect product quality. This study has a novelty by focusing on the rural roof tile industry and integrating three main variables in the analysis of product quality. The implications of this study provide practical guidance for craftsmen to manage raw materials and production processes to improve product quality, as well as support the policy of developing the roof tile industry through training and coaching. Theoretically, this study contributes to the development of product quality management theory in small industries and opens up opportunities for further research.